Malnutrition and its association with readmission and death within 7 days and 8–180 days postdischarge in older patients: a prospective observational study. Issue 11 (12th November 2017) - Sharma, Yogesh; Miller, Michelle; Kaambwa, Billingsley; Shahi, Rashmi; Hakendorf, Paul; Horwood, Chris; Thompson, Campbell
Abstract : Objective: The relationship between admission nutritional status and clinical outcomes following hospital discharge is not well established. This study investigated whether older patients' nutritional status at admission predicts unplanned readmission or death in the very early or late periods following hospital discharge. Design, setting and participants: The study prospectively recruited 297 patients ≥60 years old who were presenting to the General Medicine Department of a tertiary care hospital in Australia. Nutritional status was assessed at admission by using the Patient-Generated Subjective Global Assessment (PG-SGA) tool, and patients were classified as either nourished (PG-SGA class A) or malnourished (PG-SGA classes B and C). A multivariate logistic regression model was used to adjust for other covariates known to influence clinical outcomes and to determine whether malnutrition is a predictor for early (0–7 days) or late (8–180 days) readmission or death following discharge. Outcome measures: The impact of nutritional status was measured on a combined endpoint of any readmission or death within 0–7 days and between 8 and 180 days following hospital discharge. Results: Within 7 days following discharge, 29 (10.5%) patients had an unplanned readmission or death whereas an additional 124 (50.0%) patients reached this combined endpoint within 8–180 days postdischarge. Malnutrition was associated with a significantly higher risk of combined endpoint of readmissions or death both within 7 days (OR 4.57, 95% CI 1.69 to 12.37, P<0.001) and within 8–180 days (OR 1.98, 95% CI 1.19 to 3.28, P=0.007) following discharge and this risk remained significant even after adjustment for other covariates. Conclusions: Malnutrition in older patients at the time of hospital admission is a significant predictor of readmission or death both in the very early and in the late periods following hospital discharge. Nutritional state should be included in future risk prediction models. Trial registration number: ACTRN No. 12614000833662 ; Post-results.